Bridging the Gap Between Care and Expectation: Patient Satisfaction with Postoperative Pain Management in a Surgical Ward — A Mixed-Methods Study - Kartika, Imelda Rahmayunia; Rezkiki, Fitria Nola; Febrina, Cory; Papa, Dahlia Permata (Chakra Brahmanda Lentera Institute, 2026)
Background: Patient satisfaction is an important indicator of healthcare quality and reflects patients’ perceptions of whether healthcare services meet their expectations. Effective postoperative pain management is essential for optimal recovery and patient satisfaction; however, gaps between clinical practice and patient expectations remain underexplored, particularly in surgical wards. Methods: This study employed an explanatory sequential mixed-methods design conducted in a surgical ward of a tertiary hospital in West Sumatra, Indonesia, from January to July 2024. The quantitative phase involved 190 postoperative patients recruited using accidental sampling. Patient satisfaction with postoperative pain management was assessed using a structured modified questionnaire from NOC (Nursing Outcomes Classification), which was analyzed descriptively. Quantitative data were analyzed using descriptive and inferential statistics, including independent t-tests and one-way Analysis of Variance (ANOVA). The qualitative phase included 8 purposively selected participants who participated in in-depth interviews to explore experiences and perceptions related to postoperative pain management. Qualitative data were analyzed using thematic analysis of interview transcripts and field notes. Quantitative and qualitative findings were integrated during the interpretation stage. Ethical approval was obtained, and informed consent was secured from all participants. Results: Quantitative findings showed that 53.2% of respondents (n = 190) reported being moderately satisfied with postoperative pain management. The mean satisfaction level indicated a moderate level of satisfaction. Inferential analyses showed that satisfaction scores differed significantly across age groups (p = 0.017), whereas no significant differences were observed according to sex (p = 0.839) or educational level (p = 0.168). Qualitative analysis identified three major themes: (1) experiences of postoperative pain, (2) postoperative pain management practices, and (3) perceptions of patient satisfaction. Integration of findings revealed that although overall satisfaction was reported, patients expressed unmet expectations regarding individualized pain relief, timely pain control, and communication with healthcare professionals. Conclusion: While most patients reported satisfaction with postoperative pain management, important gaps remain between patient expectations and clinical practice. Patient satisfaction with postoperative pain management was associated with age but not with sex or educational level. Qualitative findings further demonstrated that effective communication, individualized care, and patient comfort were central experiences shaping patient satisfaction. These findings highlight the importance of combining patient-centered care with effective pain management strategies to improve postoperative care quality.